2017
DOI: 10.1021/acsami.6b15746
|View full text |Cite
|
Sign up to set email alerts
|

Red Emission B, N, S-co-Doped Carbon Dots for Colorimetric and Fluorescent Dual Mode Detection of Fe3+ Ions in Complex Biological Fluids and Living Cells

Abstract: Colorimetric and fluorescent dual mode detection methods have gained much attention in recent years; however, it is still desirable to develop new colorimetric and fluorescent dual mode nanosensors with more simple preparation procedures, low cost, and excellent biocompatibility. Herein, a colorimetric and fluorescent nanosensor based on B, N, S-co-doped carbon dots (BNS-CDs) was synthesized by one-step hydrothermal treatment of 2,5-diaminobenzenesulfonic acid and 4-aminophenylboronic acid hydrochloride. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
217
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(223 citation statements)
references
References 62 publications
6
217
0
Order By: Relevance
“…In Figure 2 a, the maximum absorption and emission band of the MMP‐CDs in PBS buffer solution exhibits at 525 and 546 nm (by using the excitation of 500 nm). As shown in Figure 2b, with the excitation wavelength changed from 400 to 520 nm, the emission intensity at 546 nm of the MMP‐CDs increases with no obvious shifting of maximum emission wavelength, indicating that the MMP‐CDs have excitation‐independent fluorescence behavior, which might be owing to relatively uniform surface and size distribution of MMP‐CDs 29. The photostability of MMP‐CDs is critical for its cellular applications.…”
Section: Resultsmentioning
confidence: 95%
“…In Figure 2 a, the maximum absorption and emission band of the MMP‐CDs in PBS buffer solution exhibits at 525 and 546 nm (by using the excitation of 500 nm). As shown in Figure 2b, with the excitation wavelength changed from 400 to 520 nm, the emission intensity at 546 nm of the MMP‐CDs increases with no obvious shifting of maximum emission wavelength, indicating that the MMP‐CDs have excitation‐independent fluorescence behavior, which might be owing to relatively uniform surface and size distribution of MMP‐CDs 29. The photostability of MMP‐CDs is critical for its cellular applications.…”
Section: Resultsmentioning
confidence: 95%
“…So far, only a few research groups have reported red emissive CDs with relatively low photoluminescent QY, poor biocompatibility, complicated synthesis procedures, broad bandwidth, and not pure red emission, so few of them had been applied to in vivo imaging . Recently, we have reported that dopamine and o ‐phenylenediamine ( o PD) were used as precursors to prepare near‐infrared photoluminescent CDs (NIR‐CDs) with QY about 26%, but these NIR‐CDs have noncontrollable structure, poor biocompatibility and broad bandwidth emission .…”
Section: Introductionmentioning
confidence: 99%
“…Their optical properties are quite similar and also dependent on the pH of the medium. Recent studies on boron and nitrogen, contents influenced luminescence properties of CNDs also support the reaction mechanism mentioned above that the presence of nitrogen content may result more contribution to π‐conjugation, thus bathochromic shift, whereas the inclusion of boron compounds in precursor may form boronate complex with adjacent hydroxyl groups and thus restricting flexibility and quenching. Moreover, X‐ray Photoelectron spectroscopic (XPS) studies on CNDs indicate the presence of three types of nitrogens ‐ pyridinic (398.1 eV), pyrrolic (399.5 eV) and tertiary nitrogen (401.6 eV) .…”
Section: Resultsmentioning
confidence: 53%